Self-repairing hydrophobic quick-drying polyurethane film-forming waterproof coating, preparation method and application thereof

CN122941289APending Publication Date: 2026-10-20NANJING LUOPU TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611247848.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

(1)快干与成膜质量的矛盾:为提升施工效率,要求涂料快速表干,但单纯使用低沸点溶剂会导致涂层流平性差、针孔和气泡缺陷,同时溶剂过快挥发造成表面结皮而内部未干,导致膜层附着力下降

Benefits of technology

(1)本发明通过低沸点复合溶剂与微胶囊潜伏固化剂的协同,实现指触表干≤5分钟、深层固化30~60分钟,施工效率较传统覆膜涂料提升50%以上。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention relates to a self-healing, hydrophobic, fast-drying polyurethane waterproof coating, its preparation method, and its application. The coating comprises the following components: 30-40 parts by weight of a main resin, 30-40 parts by weight of a composite solvent, 20-30 parts by weight of a functional additive system, 1-5 parts by weight of a coloring material, 2-8 parts by weight of a silane-terminated polyetheramine oligomer, 1-5 parts by weight of a microencapsulated isocyanate latent curing agent, 0.5-3 parts by weight of a nano-silica aerogel slurry, and 0.1-1.5 parts by weight of a fluorinated silsesquioxane. This invention is the first to synergistically use four functional components—silane-terminated polyetheramine, microencapsulated latent curing agent, nano-aerogel, and fluorinated silsesquioxane—to construct a four-in-one coating system that integrates fast-drying film formation, self-healing superhydrophobicity, gradient waterproofing with closed-cell construction, and permanent flame retardancy and toughening.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer waterproof coating technology, specifically to a self-healing, hydrophobic, and fast-drying polyurethane membrane waterproof coating with functions of quick drying, self-healing hydrophobicity, waterproof closed-cell structure, and permanent flame retardancy, as well as its preparation method and application. Background Technology

[0002] Currently, existing sponge coatings suffer from problems such as loss of elasticity with thick coatings, embrittlement due to flame retardant migration, a contradiction between fast drying and film formation quality, and poor waterproof durability. In particular, hydrophobic coatings experience irreversible wear due to friction and bending during practical use. There are currently no reports of single-component polyurethane coatings that can achieve hydrophobic self-healing through physical migration at room temperature.

[0003] Furthermore, in practical applications of polyurethane foam microwave absorbing materials, the open-cell structure of the foam easily absorbs moisture and pollutants from the environment, leading to a decrease in absorption performance and a shortened service life. Therefore, it is necessary to treat the foam surface with a closed-cell coating to impart waterproof, moisture-proof, and stain-resistant properties. However, existing technologies face the following prominent contradictions: (1) The contradiction between fast drying and film quality: In order to improve construction efficiency, the coating is required to dry quickly. However, simply using low boiling point solvents will result in poor leveling of the coating, pinholes and bubbles. At the same time, the solvent evaporates too quickly, causing the surface to form a skin while the inside is not dry, resulting in a decrease in film adhesion.

[0004] (2) The contradiction between waterproofness and flexibility: Achieving high waterproofness usually requires high cross-linking density or the introduction of rigid structure, but this will sacrifice the flexibility of the coating, causing the film to crack and fall off when bent and rubbed.

[0005] (3) The contradiction between flame retardant durability and film stability: Traditional additive flame retardants will migrate to the surface during long-term use, causing the film to become brittle and the adhesion to decrease. At the same time, the flame retardant effect will decay over time.

[0006] (4) There are no existing literature reports on the synergistic use of silane-terminated polyetheramine, microencapsulated latent curing agent, nano aerogel and fluorinated silsesquioxane in sponge-coated waterproof coatings. Summary of the Invention

[0007] To address the aforementioned problems in the prior art, the present invention aims to provide a self-healing, hydrophobic, and fast-drying polyurethane waterproof coating, its preparation method, and its application. This invention addresses the problems through a specific resin-solvent-additive system and a low-pressure thin-spray process.

[0008] To achieve the above objectives, the present invention provides the following technical solution: A self-healing, hydrophobic, and fast-drying polyurethane waterproof coating comprises the following components: 30-40 parts by weight of main resin, 30-40 parts by weight of composite solvent, 20-30 parts by weight of functional additives, 1-5 parts by weight of coloring material, 2-8 parts by weight of silane-terminated polyetheramine oligomer, 1-5 parts by weight of microencapsulated isocyanate latent curing agent, 0.5-3 parts by weight of nano-silica aerogel slurry, and 0.1-1.5 parts by weight of fluorinated silsesquioxane F-POSS; The main resin is a single-component solvent-based polyurethane resin; the functional additives include at least one of the following: additive nitrogen-phosphorus intumescent flame retardant, charring agent, inorganic flame retardant synergist, dispersant, defoamer, leveling agent, and plasticizer stabilizer.

[0009] The coating achieves rapid film formation through a dual-channel mechanism of "physical surface drying - chemical deep curing": the low-boiling-point solvent evaporates to achieve touch dryness in 1-5 minutes; the latent curing agent is activated by ambient moisture and undergoes secondary cross-linking with silane-terminated polyetheramine oligomers, completing deep curing in 30-60 minutes; the fluorinated silsesquioxane automatically migrates to the coating-air interface during the curing process to form a fluorinated monomolecule hydrophobic layer, and after the coating surface is worn, the internal F-POSS continues to migrate to the new surface, achieving room temperature self-healing hydrophobicity; the nano-silica aerogel slurry provides a micro-nano composite rough structure and fills the sponge pores, working with F-POSS to construct a gradient hydrophobic closed-pore layer.

[0010] The fluorinated silsesquioxane is a polyhedral oligomeric silsesquioxane with peripherally grafted fluorinated alkyl chains, having the general formula (RSiO). 1.5 ) n n=8, 10 or 12, and at least 50% of the R groups are -C. x H 2x+1 CF3, x=6~12. Preferably, the fluorinated silsesquioxane is fluorinated octylsilsesquioxane F-POSS8, R=-CH2CH2(CF2)7CF3, with a molecular weight of 3000~5000 g / mol.

[0011] The silane-terminated polyetheramine oligomer is a polyetheramine oligomer with end groups containing trimethoxysilane or triethoxysilane, and a number-average molecular weight of 500–3000 g / mol. The ether oxygen atoms of its polyether backbone interact with the F-POSS silicon-oxygen cage through hydrogen bonding, promoting the directional migration of F-POSS to the coating surface, increasing the migration efficiency by more than 40%.

[0012] The single-component solvent-based polyurethane resin includes 9055H-2 or MR-917, the additive nitrogen-phosphorus intumescent flame retardant includes SW-627s, and the charring agent includes CW-100G. The dispersant includes BYK-163, the defoamer includes BYK-066N, the leveling agent includes BYK-331, and the plasticizer and stabilizer includes epoxidized soybean oil; The coloring material includes at least one of titanium dioxide and color paste; the color paste includes ultramarine blue paste.

[0013] The microencapsulated isocyanate latent curing agent uses polyurea or polyurethane as the shell material and aliphatic or alicyclic polyisocyanate as the core material, with a particle size of 5–30 μm. The shell material ruptures and releases active -NCO groups under the action of solvent evaporation and moisture penetration.

[0014] The nano-silica aerogel slurry is a pre-dispersion slurry of hydrophobic aerogel in a composite solvent, with a solid content of 10-25%, an original aerogel particle size of 20-50 nm, and a specific surface area of ​​600-1000 m². 2 / g. Aerogel fills the surface of the sponge with openings and works in synergy with F-POSS to achieve no water leakage after 120 minutes of 0.3MPa water pressure and a water absorption rate of ≤3% after 24 hours.

[0015] Furthermore, the inorganic flame retardant synergist includes at least one of aluminum hydroxide and a reactive phosphorus-containing flame retardant polyol. The reactive phosphorus-containing flame retardant polyol has a hydroxyl value of 200–400 mg KOH / g and a phosphorus content of 8–15 wt%, and permanently fixes the phosphorus element in the network through the participation of hydroxyl groups in polyurethane crosslinking. When compounded with additive nitrogen-phosphorus intumescent flame retardant, charring agent, and aluminum hydroxide, the oxygen index is ≥32%, and the flame retardancy does not decrease after aging at 60°C for 30 days, and there are no cracks after 180° bending.

[0016] Preferably, the reactive phosphorus-containing flame-retardant polyol has a hydroxyl value of 320 mg KOH / g and a phosphorus content of 12 wt%.

[0017] The composite solvent is at least three of acetone, ethyl acetate, xylene, and N,N-dimethylformamide; wherein the proportion of low-boiling-point solvent with a boiling point ≤80℃ is ≥50%, and the proportion of medium-high-boiling-point solvent with a boiling point ≥130℃ is 10-25%, thereby constructing a volatile gradient that achieves fast drying and leveling.

[0018] The technical principle of this invention's self-healing, hydrophobic, and fast-drying polyurethane waterproof coating includes: Fast-drying film-forming mechanism: Low-boiling-point solvents achieve touch-drying in 3 minutes; microcapsule latent curing agents slowly release -NCO under moisture and capillary action, reacting with the terminal amine / hydroxyl groups of silane-terminated polyetheramines, completing deep cross-linking in 30-60 minutes, significantly shortening the construction cycle.

[0019] Self-healing hydrophobic mechanism: F-POSS molecules automatically migrate to the surface during curing, with the fluorine-containing long chains aligning outwards to form a liquid-like monolayer with an initial contact angle ≥150°. After surface wear, the internal F-POSS continues to migrate to the new surface under thermodynamic drive, with a contact angle recovery rate ≥97% after standing at room temperature for 24 hours.

[0020] The dual role of silane-terminated polyetheramine: it is both a flexible crosslinking agent for moisture curing and a "molecular guide band" formed by the hydrogen bonding between the ether oxygen bond and F-POSS, enabling F-POSS to migrate efficiently to the surface along the polyether chain segment.

[0021] Gradient waterproof closed-cell mechanism: Nano-aerogel fills the sponge opening and provides a micro-nano rough structure, serving as an anchor point and reservoir for F-POSS; F-POSS provides molecular-level low surface energy modification, and the two work together to make the coating impermeable to water for 120 minutes at 0.3MPa, with a water absorption rate of ≤2.8%.

[0022] Permanent flame retardant and toughening mechanism: The reactive phosphorus-containing polyol fixes the phosphorus element with covalent bonds to prevent migration. It works synergistically with the additive intumescent flame retardant and aluminum hydroxide. The oxygen index is ≥32%. After aging, the film layer can still be bent 180° without cracks.

[0023] The preparation method of the self-healing hydrophobic quick-drying polyurethane membrane waterproof coating of the present invention includes the following steps: (1) Add nano silica aerogel slurry, additive nitrogen and phosphorus intumescent flame retardant, charring agent, inorganic flame retardant synergist, and coloring material to a portion of the composite solvent, disperse at 1000-1500 rpm for 30-40 minutes until the fineness is ≤25μm to obtain pre-dispersed slurry; (2) Add the main resin, remaining solvent, functional additives, and reactive flame-retardant polyol, and disperse at 800-1000 rpm for 15-20 minutes; (3) Cool to 400-600 rpm and ≤40℃, then add silane-terminated polyetheramine, microcapsule latent curing agent, and pre-dissolved F-POSS solution sequentially, and disperse for 5-10 minutes; wherein, F-POSS is pre-dissolved in a fluorinated solvent or ketone solvent and added in solution form to ensure uniform dispersion. (4) Filter the material through a 200-mesh filter to obtain the final product.

[0024] The self-healing, hydrophobic, and fast-drying polyurethane waterproof coating of this invention can be used in the waterproofing and closed-cell treatment of polyurethane sponge wave-absorbing materials.

[0025] The spraying process uses an HVLP spray gun, which is cured at room temperature. The HVLP spray gun has a nozzle diameter of 1.5-2.5mm, a spraying air pressure of 1.5-3.0 bar, a spraying distance of 15-30cm, 2-4 spray passes, a film thickness of 10-25μm per pass, and a flash-off time of 3-8 minutes between passes. The spraying environment temperature is 15-35℃, and the relative humidity is 40-80%.

[0026] Compared with the prior art, the beneficial effects of the present invention are: (1) This invention achieves surface drying in ≤5 minutes and deep curing in 30-60 minutes by combining low-boiling-point composite solvent with microcapsule latent curing agent, thereby improving the construction efficiency by more than 50% compared with traditional coatings.

[0027] (2) The present invention imparts a self-healing hydrophobic function to the coating at room temperature by means of the self-migration properties of fluorinated silsesquioxane (F-POSS), with an initial contact angle ≥150°, still ≥130° after 500 rubs, and a 24h static recovery rate ≥97%.

[0028] (3) This invention achieves water impermeability at 0.3MPa / 120min and water absorption rate ≤3% at 24h through gradient synergy between nano silica aerogel and F-POSS, thus completely solving the moisture absorption problem of sponge wave-absorbing materials.

[0029] (4) The present invention uses a reactive phosphorus-containing flame-retardant polyol and an additive intumescent flame retardant to achieve an oxygen index ≥32%. After aging at 60°C for 30 days, the flame retardancy is not reduced and there are no cracks when bent at 180°.

[0030] (5) This invention is the first to use four functional components, namely silane-terminated polyetheramine, microcapsule latent curing agent, nano aerogel and fluorinated silsesquioxane, in synergy to construct a coating system that integrates fast drying film formation, self-healing superhydrophobicity, gradient waterproof closed pores, and permanent flame retardant toughening. No relevant published literature has been found in the prior art. Detailed Implementation

[0031] The technical solution of the present invention will be clearly and completely described below with reference to embodiments and comparative examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.

[0033] Examples 1-2 are the basic schemes, and examples 3-4 are the preferred schemes of the present invention.

[0034] The product brands and manufacturers used in the following examples and comparative examples are as follows: Resin: 9055H-2 (single-component solvent-based polyurethane resin), Hubei Chuangxin Polyurethane Materials Co., Ltd.

[0035] Resin: MR-917 (single-component solvent-based polyurethane resin), Xuzhou Yihuiyang New Material Co., Ltd.

[0036] Composite solvents: acetone (industrial grade), ethyl acetate (industrial grade), xylene (industrial grade), N,N-dimethylformamide (DMF, industrial grade), butyl acetate (industrial grade), Sinopharm Chemical Reagent Co., Ltd.

[0037] Flame retardant: SW-627s (nitrogen-phosphorus intumescent flame retardant), Shandong Xiucheng Chemical Co., Ltd. (or equivalent product).

[0038] Carbonizing agent: CW-100G (carbonizing agent), Shandong Xiucheng Chemical Co., Ltd. (or equivalent product).

[0039] Dispersant: BYK-163 (wetting and dispersing agent), BYK Chemicals.

[0040] Defoamer: BYK-066N (defoamer), BYK Chemicals.

[0041] Leveling agent: BYK-331 (leveling agent), BYK Chemicals.

[0042] Plasticizer / stabilizer: Epoxidized soybean oil, commercially available (industrial grade).

[0043] The reactive phosphorus-containing flame-retardant polyol has a hydroxyl value of 320 mg KOH / g and a phosphorus content of 12wt%. It can be synthesized according to conventional methods in this field (journal article "Synthesis of Phosphorus-Containing Polyols and Their Flame-Retardant Modified PUR Rigid Foam") or purchased on a custom basis.

[0044] Titanium dioxide: Rutile type, industrial grade, commercially available, such as from Lomon Billions Group.

[0045] Universal ultramarine blue pigment, commercially available pigment (used for color mixing).

[0046] Silane-terminated polyetheramine oligomers: Trimethoxysilane-terminated polyetheramines (Mn≈1500 g / mol) can be prepared by conventional methods in the field (journal article "Silane-modified polyethers based on Michael addition reaction and their synthesis methods"), or commissioned for custom synthesis.

[0047] Microencapsulated isocyanate latent curing agent: HDI trimer as core material and polyurea as shell material (average particle size 15μm), can be prepared by conventional methods in the field (refer to the preparation process of microencapsulated phase change materials or self-healing microcapsules, such as the journal article "Preparation of cross-linked polyurea capsule wall microcapsules"), or commissioned for customization.

[0048] Nano-silica aerogel slurry: Hydrophobic aerogel slurry, solid content 18%, native particle size 30nm, specific surface area 800m² 2 / g, can be prepared by pre-dispersion according to conventional methods in the field (such as "A method for preparing hydrophobic nano silica aerogel aqueous slurry"), or commercially available.

[0049] Fluorinated silsesquioxanes: Fluorinated octyl silsesquioxanes (F-POSS8, R= -CH2CH2(CF2)7CF3, molecular weight approximately 3000–5000 g / mol) can be synthesized according to literature methods (such as prism-type POSS technology, "Fluorinated Polyhedral Oligomeric Silsesquioxanes (F-POSS)") or commissioned for custom production.

[0050] Fluorinated solvent (used for pre-dissolving F-POSS): hexafluoroxylene (hexafluorom-xylene, CAS: 1076-61-5), commercially available.

[0051] Example 1

[0052] A method for preparing a polyurethane coating includes the following steps: (1) Premix 10 parts by weight of ethyl acetate (industrial grade, Sinopharm Chemical Reagent Co., Ltd.), 10 parts by weight of xylene (industrial grade, Sinopharm Chemical Reagent Co., Ltd.), and 5 parts by weight of N,N-dimethylformamide (DMF, industrial grade, Sinopharm Chemical Reagent Co., Ltd.) for 5 minutes to obtain a total of 25 parts by weight of mixed solvent; mix 25 parts by weight of the mixed solvent, 15 parts by weight of nitrogen-phosphorus intumescent flame retardant (brand: SW-627s, Shandong Xiucheng Chemical Co., Ltd.), and charring agent (brand: 3.75 parts by weight of CW-100G (Shandong Xiucheng Chemical Co., Ltd.), 6.25 parts by weight of aluminum hydroxide (industrial grade, Aluminum Corporation of China Limited), 0.375 parts by weight of titanium dioxide (rutile type, grade: R-996, Lomon Billions Group Co., Ltd.), and 2.625 parts by weight of general ultramarine blue paste (industrial grade, Shiming Technology Co., Ltd.) were added to a high-speed disperser and dispersed at 1200 rpm for 35 minutes. The fineness was tested to be ≤25μm to obtain a well dispersed solution. (2) Add 35 parts by weight of single-component solvent-based polyurethane resin (brand: 9055H-2, Hubei Chuangxin Polyurethane Materials Co., Ltd.), 0.5 parts by weight of defoamer (brand: BYK-066N, BYK Chemical), and 0.3 parts by weight of leveling agent (brand: BYK-331, BYK Chemical), and disperse at 1000 rpm for 10 minutes to obtain polyurethane coating; (3) Using a 2.0mm diameter HVLP spray gun and an air pressure of 2.0bar, spray the coating at a distance of 25cm from the sponge substrate soaked in the microwave absorbing coating, and cure at room temperature for 24 hours to obtain polyurethane coated microwave absorbing material.

[0053] Example 2

[0054] A method for preparing a polyurethane coating includes the following steps: (1) 15 parts by weight of ethyl acetate (industrial grade, Sinopharm Chemical Reagent Co., Ltd.) and 15 parts by weight of butyl acetate (industrial grade, Sinopharm Chemical Reagent Co., Ltd.) were premixed for 5 minutes to obtain a total of 30 parts by weight of mixed solvent; 30 parts by weight of the mixed solvent, 15 parts by weight of ammonium polyphosphate (brand name: APP-2, degree of polymerization n≥1000, type II, Hangzhou Jiersi Flame Retardant Chemical Co., Ltd.), 5 parts by weight of melamine (industrial grade, Sichuan Chuanhua Group Co., Ltd.), 5 parts by weight of pentaerythritol (industrial grade, Hubei Yihua Group Co., Ltd.), 0.375 parts by weight of titanium dioxide (rutile type, brand name: R-996, Longbai Group Co., Ltd.), and 2.625 parts by weight of general ultramarine blue paste (industrial grade, Shiming Technology Co., Ltd.) were added to a high-speed disperser and dispersed at 1200 rpm for 35 minutes. The fineness was tested to be ≤25 μm to obtain a well dispersed solution; (2) Add 35 parts by weight of single-component solvent-based polyurethane resin (brand: MR-917, Xuzhou Yihuiyang New Material Co., Ltd.), 0.5 parts by weight of defoamer (brand: BYK-066N, BYK Chemical), and 0.3 parts by weight of leveling agent (brand: BYK-331, BYK Chemical), and disperse at 1000 rpm for 10 minutes to obtain polyurethane coating; (3) Using a 2.0mm diameter HVLP spray gun and an air pressure of 2.0bar, spray the coating at a distance of 25cm from the sponge substrate soaked in the microwave absorbing coating, and cure at room temperature for 24 hours to obtain polyurethane coated microwave absorbing material.

[0055] Example 3

[0056] A method for preparing a fast-drying polyurethane waterproof coating includes the following steps: (1) The nano-silica aerogel slurry (hydrophobic, solid content 18%, original particle size 30nm, specific surface area 800m²) 22 parts by weight of acetone (industrial grade, China National Chemical Corporation), 15 parts by weight of nitrogen-phosphorus intumescent flame retardant (brand: SW-627s, Shandong Xiucheng Chemical Co., Ltd.), 5 parts by weight of charring agent (brand: CW-100G, Shandong Xiucheng Chemical Co., Ltd.), 8 parts by weight of aluminum hydroxide (industrial grade, Aluminum Corporation of China Limited), 0.375 parts by weight of titanium dioxide (rutile type, brand: R-996, Lomon Billions Group Co., Ltd.), and 2.625 parts by weight of general ultramarine blue paste (industrial grade, Shiming Technology Co., Ltd.) were added to a mixed solvent consisting of 20 parts by weight of acetone (industrial grade, Sinopharm Chemical Reagent Co., Ltd.), 15 parts by weight of ethyl acetate (industrial grade, Sinopharm Chemical Reagent Co., Ltd.), and 5 parts by weight of xylene (industrial grade, Sinopharm Chemical Reagent Co., Ltd.). The mixture was dispersed at 1200 rpm for 35 minutes, and the fineness was tested to be ≤20 μm to obtain a pre-dispersed slurry. (2) 35 parts by weight of single-component solvent-based polyurethane resin (brand: 9055H-2, Hubei Chuangxin Polyurethane Materials Co., Ltd.), 3 parts by weight of epoxidized soybean oil (industrial grade, Guangzhou Xinjinlong Plastic Additives Co., Ltd.), 10 parts by weight of reactive phosphorus-containing flame-retardant polyol (hydroxyl value 320 mg KOH / g, phosphorus content 12wt%, which can be synthesized according to conventional methods in this field or customized commercially, such as Wansheng Co., Ltd.), and 0.8 parts by weight of wetting and dispersing agent (brand: BYK-163, BYK Chemical) were added to the pre-dispersed slurry and dispersed at 900 rpm for 18 minutes. (3) Reduce the rotation speed to 500 rpm, control the material temperature to ≤35℃, and add 5 parts by weight of silane-terminated polyetheramine oligomer (trimethoxysilane-terminated, number-average molecular weight Mn≈1500 g / mol, which can be synthesized by conventional methods in the field or commissioned to Huntsman / Momentive) in sequence, 3 parts by weight of microencapsulated isocyanate latent curing agent (HDI trimer as core material, polyurea as shell material, average particle size 15μm, which can be prepared by conventional methods in the field or commissioned to customize) 0.5 parts by weight of defoamer (brand: BYK-066N, BYK Chemical) and 0.3 parts by weight of leveling agent (brand: BYK-331, BYK Chemical), and disperse for 8 minutes; (4) The material is filtered through a 200-mesh filter, sealed and packaged to obtain the quick-drying polyurethane waterproof coating.

[0057] (5) Using a 2.0mm diameter HVLP spray gun, with an air pressure of 2.0 bar and a distance of 25cm, spray three coats onto the sponge substrate (P500 type) that has been impregnated with microwave absorbing coating and dried. Each coat has a film thickness of 15-20μm. Flash dry for 5 minutes between coats and cure at room temperature for 24 hours.

[0058] Example 4

[0059] A method for preparing a self-healing, hydrophobic, and fast-drying polyurethane waterproof coating includes the following steps: (1) Pre-dispersion: The nano-silica aerogel slurry (hydrophobic, solid content 18%, original particle size 30nm, specific surface area 800m²) was dispersed. 2 2.5 parts by weight of a nitrogen-phosphorus intumescent flame retardant (brand: SW-627s, Shandong Xiucheng Chemical Co., Ltd.), 12 parts by weight of a charring agent (brand: CW-100G, Shandong Xiucheng Chemical Co., Ltd.), 4 parts by weight of an aluminum hydroxide (industrial grade, Aluminum Corporation of China Limited), 6 parts by weight of a titanium dioxide (rutile type, brand: R-996, Lomon Billions Group Co., Ltd.), and 2.625 parts by weight of a general ultramarine blue paste (industrial grade, Shiming Technology Co., Ltd.) were added to a mixed solvent consisting of 18 parts by weight of acetone (industrial grade, Sinopharm Chemical Reagent Co., Ltd.), 14 parts by weight of ethyl acetate (industrial grade, Sinopharm Chemical Reagent Co., Ltd.), and 6 parts by weight of xylene (industrial grade, Sinopharm Chemical Reagent Co., Ltd.). The mixture was dispersed at 1200 rpm for 35 minutes, and the fineness was tested to be ≤20 μm to obtain a pre-dispersed slurry. (2) Main mixture: Add 34 parts by weight of single-component solvent-based polyurethane resin (brand: 9055H-2, Hubei Chuangxin Polyurethane Materials Co., Ltd.), 3 parts by weight of epoxidized soybean oil (industrial grade, Guangzhou Xinjinlong Plastic Additives Co., Ltd.), 8 parts by weight of reactive phosphorus-containing flame retardant polyol (hydroxyl value 320 mg KOH / g, phosphorus content 12wt%, can be synthesized according to conventional methods in this field or customized commercially, such as Wansheng Co., Ltd.), and 0.8 parts by weight of wetting and dispersing agent (brand: BYK-163, BYK Chemicals), and disperse at 900 rpm for 18 minutes; (3) F-POSS pre-dissolution: Dissolve 0.6 parts by weight of fluorinated octylsilsesquioxane (brand name: F-POSS8, R= -CH2CH2(CF2)7CF3, molecular weight about 3000~5000 g / mol, Hybrid Plastics, USA) in 1 part by weight of hexafluoroxylene (CAS: 1076-61-5, Sigma-Aldrich) and stir until completely dissolved to obtain F-POSS pre-solution; (4) Addition of functional components: Reduce the speed to 500 rpm, control the material temperature to ≤35℃, and add 5 parts by weight of silane-terminated polyetheramine oligomer (trimethoxysilane-terminated, number-average molecular weight Mn≈1500 g / mol, which can be synthesized by conventional methods in the field or commissioned to Huntsman / Momentive) in sequence, 2.5 parts by weight of microencapsulated isocyanate latent curing agent (HDI trimer as core material, polyurea as shell material, average particle size 15μm, which can be prepared by conventional methods in the field or commissioned to customize), F-POSS pre-solution from step (3), 0.5 parts by weight of defoamer (brand name: BYK-066N, BYK Chemical), and 0.3 parts by weight of leveling agent (brand name: BYK-331, BYK Chemical), and disperse for 8 minutes; (5) The material is filtered through a 200-mesh filter, sealed and packaged to obtain the self-healing hydrophobic quick-drying polyurethane membrane waterproof coating; (6) Spraying: Using a 2.0mm diameter HVLP spray gun, with an air pressure of 2.0bar, spray three coats at a distance of 25cm from the sponge substrate (P500 type) that has been impregnated with and dried with the microwave absorbing coating. Each coat has a film thickness of 15-20μm. Flash dry for 5 minutes between coats and cure at room temperature for 24 hours to obtain a self-healing hydrophobic fast-drying polyurethane waterproof coating.

[0060] To highlight the beneficial effects of the present invention, the following comparative experiments are provided.

[0061] Comparative Example 1: Preparation of polyurethane coatings using a single solvent (DMF) instead of mixed solvents This comparative example differs from Example 1 only in that the mixed solvent of ethyl acetate, xylene, and DMF in Example 1 is replaced with an equal amount of the single solvent DMF (N,N-dimethylformamide, industrial grade, Sinopharm Chemical Reagent Co., Ltd.), and the volatilization gradient strategy of combining low-boiling-point and medium-to-high-boiling-point solvents is not used. All other components and their amounts are exactly the same as in Example 1. The specific preparation steps are as follows: (1) 25 parts by weight of solvent DMF (N,N-dimethylformamide, industrial grade, Sinopharm Chemical Reagent Co., Ltd.), 15 parts by weight of nitrogen-phosphorus intumescent flame retardant (brand: SW-627s, Shandong Xiucheng Chemical Co., Ltd.), 3.75 parts by weight of charring agent (brand: CW-100G, Shandong Xiucheng Chemical Co., Ltd.), 6.25 parts by weight of aluminum hydroxide (industrial grade, Aluminum Corporation of China Limited), 0.375 parts by weight of titanium dioxide (rutile type, brand: R-996, Lomon Billions Group Co., Ltd.), and 2.625 parts by weight of general ultramarine blue paste (industrial grade, Shiming Technology Co., Ltd.) were added to a high-speed disperser and dispersed at 1200 rpm for 35 minutes. The fineness was tested to be ≤25 μm to obtain a well dispersed solution. (2) Add 35 parts by weight of single-component solvent-based polyurethane resin (brand: 9055H-2, Hubei Chuangxin Polyurethane Materials Co., Ltd.), 0.5 parts by weight of defoamer (brand: BYK-066N, BYK Chemical), and 0.3 parts by weight of leveling agent (brand: BYK-331, BYK Chemical), and disperse at 1000 rpm for 10 minutes to obtain polyurethane coating; (3) Using a 2.0mm diameter HVLP spray gun and an air pressure of 2.0bar, spray the coating at a distance of 25cm from the sponge substrate soaked in the microwave absorbing coating, and cure at room temperature for 24 hours to obtain polyurethane coated microwave absorbing material.

[0062] Existing performance defects: (1) DMF is not a fast-drying solvent, and a single solvent cannot adjust the surface drying rate, which greatly prolongs the surface drying time of the product; (2) Although DMF has good solubility for polyurethane, its own hygroscopicity makes curing difficult, and the spraying cannot achieve the film coating effect, resulting in serious sagging; (3) VOC 580g / L exceeds the standard, resulting in poor environmental performance.

[0063] Comparative Example 2: Preparation of Polyurethane Microwave Absorbing Coating without Flame Retardant Addition The only difference between this comparative example and Example 1 is that no flame retardant components (including nitrogen-phosphorus intumescent flame retardant SW-627s, charring agent CW-100G, and aluminum hydroxide) are added. Furthermore, to maintain the basic filling and coloring properties of the coating, an equal amount of filler is used to replace the omitted flame retardants. All other components and their amounts remain comparable to those in Example 1. The specific preparation steps are as follows: (1) 16 parts by weight of ethyl acetate (industrial grade, Sinopharm Chemical Reagent Co., Ltd.), 16 parts by weight of xylene (industrial grade, Sinopharm Chemical Reagent Co., Ltd.), and 8 parts by weight of N,N-dimethylformamide (DMF, industrial grade, Sinopharm Chemical Reagent Co., Ltd.) were premixed for 5 minutes to obtain a total of 40 parts by weight of mixed solvent; 40 parts by weight of the mixed solvent, 6 parts by weight of calcium carbonate (light, industrial grade, Jiangxi Guangyuan Chemical Co., Ltd.), 0.375 parts by weight of titanium dioxide (rutile type, grade: R-996, Longmang Baililian Group Co., Ltd.), and 2.625 parts by weight of general ultramarine blue paste (industrial grade, Shiming Technology Co., Ltd.) were added to a high-speed disperser and dispersed at 1200 rpm for 35 minutes. The fineness was tested to be ≤25 μm to obtain a well dispersed solution; (2) Add 35 parts by weight of single-component solvent-based polyurethane resin (brand: 9055H-2, Hubei Chuangxin Polyurethane Materials Co., Ltd.), 0.5 parts by weight of defoamer (brand: BYK-066N, BYK Chemical), and 0.3 parts by weight of leveling agent (brand: BYK-331, BYK Chemical), and disperse at 1000 rpm for 10 minutes to obtain polyurethane coating; (3) Using a 2.0mm diameter HVLP spray gun and an air pressure of 2.0bar, spray the coating at a distance of 25cm from the sponge substrate soaked in the microwave absorbing coating, and cure at room temperature for 24 hours to obtain polyurethane coated microwave absorbing material.

[0064] Existing performance defects: Oxygen index drops below 19, no UL94 rating.

[0065] Comparative Example 3 This comparative example provides a method for preparing a polyurethane coating, which differs from Example 1 only in that the dispersant BYK-163 is not added.

[0066] Existing performance defects: agglomeration of solid flame retardants and titanium dioxide, resulting in reduced flame retardant effect, obvious particle texture on the sprayed surface, and uneven film layer.

[0067] Comparative Example 4 This comparative example provides a method for preparing a polyurethane coating. The only difference from Example 1 is that the plasticizer tributyl citrate is replaced with the traditional plasticizer dioctyl phthalate.

[0068] Existing performance defects: The coating migrates and becomes sticky after 24 hours, with adhesion decreasing to 1.2 N / cm. 2 .

[0069] Comparative Example 5 The only difference between this comparative example and Example 3 is that no silane-terminated polyetheramine oligomer and microencapsulated isocyanate latent curing agent are added.

[0070] Existing performance defects: the surface drying time is extended to 15 minutes, the deep layer is still not fully cured after 24 hours, the film hardness is insufficient, and water seepage occurs after 30 minutes under 0.3MPa water pressure.

[0071] Comparative Example 6 The only difference between this comparative example and Example 3 is that the reactive phosphorus-containing flame-retardant polyol is replaced with an equal amount of additive flame retardant APP-2.

[0072] Existing performance defects: After aging at 60℃ for 30 days, cracks appeared in the film layer when bent at 180°, the oxygen index dropped from 32% to 26%, and the adhesion decreased from 3.5 N / cm. 2 Reduced to 2.0 N / cm 2 .

[0073] Comparative Example 7 The only difference between this comparative example and Example 3 is that the nano-silica aerogel slurry is replaced with an equal amount of organic bentonite.

[0074] Existing performance defects: The water absorption rate increased from 2.8% to 8.5% in 24 hours; water seepage occurred after 90 minutes under 0.3MPa water pressure; and the contact angle of the membrane surface decreased from 138° to 72°.

[0075] Comparative Example 8 The only difference between this comparative example and Example 4 is that no fluorinated silsesquioxane (F-POSS) is added.

[0076] The preparation steps are the same as in Example 4, except that the F-POSS solution and its pre-dissolution steps are omitted in steps (3) and (4), and the rest are exactly the same.

[0077] Existing performance defects: The initial water contact angle of the coating is only 138°, which drops to 72° after 100 rubs, and no hydrophobicity is restored after 24 hours of standing; after 500 rubs, the contact angle drops to below 50°, and the hydrophobic function is lost.

[0078] Comparative Example 9 The only difference between this comparative example and Example 4 is that the silane-terminated polyetheramine oligomer is replaced with an equal part by weight of ordinary polyether polyol (molecular weight of about 2000, which does not have a silane-terminated structure).

[0079] Existing performance defects: F-POSS is unevenly dispersed in the coating, with localized enrichment and depletion zones appearing on the surface. The initial contact angle is only 142°, decreasing to 65° after 500 cycles of friction, and the recovery rate after 24 hours of rest is only 12%. This indicates that without the hydrogen bonding guidance of silane-terminated polyetheramine, F-POSS cannot effectively migrate directionally to the surface.

[0080] Test Example 1 The comparison test results for fast-drying performance are shown in Table 1. The "touch dry time" was measured using the touch method (Method B) in GB / T 1728-2020. The "sandable time" was measured using the filter paper method (Method A) in GB / T 1728-2020, used to determine the actual drying time of the coating. The "complete curing time" can be determined with reference to GB / T 1728-2020, and is typically judged more rigorously using the cotton ball method or the blade method.

[0081] Table 1

[0082] Test Example 2 The performance of the polyurethane coatings prepared in the examples and comparative examples was tested, as follows: (1) Flame retardant performance test: The test shall be conducted in accordance with GB / T 2408-2008.

[0083] (2) Mechanical performance test: The results are shown in Table 2. Among them, the oxygen index was determined by standard GB / T 2406.2-2009 "Determination of burning behavior of plastics by oxygen index method - Part 2: Room temperature test"; the adhesion was determined by standard GB / T 5210-2006 "Paint and varnish pull-off adhesion test"; and the 180° bending was determined by standard GB / T 6742-2007 "Paint and varnish bending test (cylindrical shaft)".

[0084] Table 2

[0085] Test Example 3 The hydrophobic self-healing properties are shown in Table 3. The contact angle was measured according to GB / T 30447-2013, "Methods for Measuring Contact Angle of Nanofilms".

[0086] 500 friction cycles: Operating procedure: Fix the test plate on the friction testing machine and perform 500 friction treatments on the coating surface under the specified load and friction medium.

[0087] Measurement after friction: After friction is completed, gently remove the surface debris with compressed air or a soft brush, and measure the water contact angle in the friction area according to the contact angle measurement method described above.

[0088] Recovery rate after 24 hours of rest: Specific procedure: After 500 rubbing cycles, the test plate was left to stand for 24 hours in a standard environment of room temperature (23±2℃) and relative humidity (50±5)%. After standing for 24 hours, the water contact angle was measured at the same location in the previously rubbed area using the contact angle measurement method described above.

[0089] Recovery rate (%) = Contact angle after 24 hours of rest / Initial contact angle × 100%.

[0090] Table 3

[0091] Test Example 4 The waterproof performance comparison test results are shown in Table 4. The standard GB / T 19250-2013 "Polyurethane Waterproof Coatings" was adopted.

[0092] Impermeability: The test shall be conducted in accordance with Clause 6.12 of GB / T 19250-2013 (the test method refers to Chapter 15 of GB / T16777-2008), with a test pressure of 0.3 MPa and a holding time of 120 min. If no water seepage is observed in any of the three specimens, the specimens shall be deemed to be qualified.

[0093] Water absorption rate: The test shall be conducted in accordance with Clause 6.15 of GB / T 19250-2013. The specimen shall be soaked in water at (23±2)℃ for 24 hours, removed, dried and weighed immediately to calculate the water absorption rate.

[0094] Table 4

[0095] Test Example 5 The waterproof coating prepared in Example 4 was tested according to the following standards: viscosity was determined according to GB / T 10247-2008; solid content was determined according to GB / T 1725-2007; fineness was determined according to GB / T 1724-2019; surface drying time was determined according to GB / T 1728-2020; film thickness was determined according to GB / T 13452.2-2008; oxygen index was determined according to GB / T 2406.2-2009; aging resistance was determined according to GB / T 1865-2009; damp heat resistance was determined according to GB / T 1740-2007; impermeability and water absorption were determined according to GB / T 19250-2013; adhesion was determined according to GB / T 5210-2006 and corresponding methods.

[0096] Table 5

[0097] The results of the above embodiments, comparative examples, and test examples clearly demonstrate that the self-healing, hydrophobic, and fast-drying polyurethane membrane waterproof coating of the present invention has the following significant advantages over the prior art: (1) Rapid film formation and efficient construction: The low-boiling-point solvent evaporates to achieve touch dryness in 3-5 minutes, and the moisture-triggered secondary cross-linking of microencapsulated isocyanate latent curing agent and silane-terminated polyetheramine oligomer completes deep curing in 30-60 minutes, shortening the time from spraying to packing to less than 4 hours. The complete construction time of a single P500 product is ≤12 minutes, which greatly improves production efficiency.

[0098] (2) Excellent waterproof and closed-cell performance: The introduction of nano silica aerogel slurry creates a superhydrophobic surface with "lotus effect". The water contact angle of the coating is ≥138°. According to GB19250-2013, it can maintain no water seepage for 120 minutes under 0.3MPa water pressure and the water absorption rate is ≤3% in 24 hours. It completely solves the problem of moisture absorption and performance degradation caused by the open-cell structure of polyurethane sponge wave absorbing material.

[0099] (3) Permanent flame retardancy and long-lasting flexibility: Through the triple synergy of reactive phosphorus-containing flame retardant polyol, additive nitrogen and phosphorus intumescent flame retardant and aluminum hydroxide, the oxygen index can reach more than 32%; at the same time, the reactive flame retardant is fixed in the polymer network in the form of covalent bonds. After 30 days of thermal oxygen aging at 60℃, the flame retardant performance has not decayed, and the film layer is still free from cracks when bent at 180°, thus eliminating the common problem of migration and embrittlement of traditional additive flame retardants.

[0100] (4) Comprehensive performance fully meets and exceeds the technical specifications: The coating of this invention meets or exceeds the requirements of the "Technical Specification V1.0 for Coating for Polyurethane Wave Absorbing Materials" in all 13 indicators, including viscosity, solid content, fineness, surface drying time, film thickness, adhesion, bending performance, elastic tear resistance, aging resistance, damp heat resistance, impermeability and water absorption.

[0101] (5) Novel composition and mechanism: This invention is the first to synergistically use four functional components—silane-terminated polyetheramine, microencapsulated latent curing agent, nano-aerogel, and fluorinated silsesquioxane—to construct a polyurethane sponge coating with fast-drying film formation, self-healing superhydrophobicity, gradient waterproofing, closed-cell structure, and permanent flame retardant toughening. Unpredictable synergistic effects, such as hydrogen bond-guided migration and reservoir-based slow release, exist among the components, significantly outperforming the effects of individual or partial combinations, demonstrating outstanding substantive features and significant progress.

[0102] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A self-healing, hydrophobic, quick-drying polyurethane membrane waterproof coating, characterized in that, It contains the following components: 30-40 parts by weight of main resin, 30-40 parts by weight of composite solvent, 20-30 parts by weight of functional additives, 1-5 parts by weight of coloring material, 2-8 parts by weight of silane-terminated polyetheramine oligomer, 1-5 parts by weight of microencapsulated isocyanate latent curing agent, 0.5-3 parts by weight of nano-silica aerogel slurry, and 0.1-1.5 parts by weight of fluorinated silsesquioxane F-POSS; The main resin is a single-component solvent-based polyurethane resin; the functional additives include at least one of the following: additive nitrogen-phosphorus intumescent flame retardant, charring agent, inorganic flame retardant synergist, dispersant, defoamer, leveling agent, and plasticizer stabilizer.

2. The self-healing, hydrophobic, quick-drying polyurethane membrane waterproof coating according to claim 1, characterized in that: The fluorinated silsesquioxane is a polyhedral oligomeric silsesquioxane with a peripherally grafted fluorinated alkyl chain, and its general formula is (RSiO). 1.5 ) n n=8, 10 or 12, and at least 50% of the R groups are -C. x H 2x+1 CF3, x = 6~12.

3. The self-healing, hydrophobic, quick-drying polyurethane membrane waterproof coating according to claim 2, characterized in that: The fluorinated silsesquioxane is fluorinated octylsilsesquioxane F-POSS8, R=-CH2CH2(CF2)7CF3, with a molecular weight of 3000-5000 g / mol.

4. The self-healing, hydrophobic, quick-drying polyurethane waterproof coating according to claim 1, characterized in that: The single-component solvent-based polyurethane resin includes 9055H-2 or MR-917, the additive nitrogen-phosphorus intumescent flame retardant includes SW-627s, and the charring agent includes CW-100G. The dispersant includes BYK-163, the defoamer includes BYK-066N, the leveling agent includes BYK-331, and the plasticizer stabilizer includes epoxidized soybean oil; The coloring material includes at least one of titanium dioxide and color paste; the color paste includes ultramarine blue paste. The silane-terminated polyetheramine oligomer is a polyetheramine oligomer with end groups containing trimethoxysilane or triethoxysilane, and a number average molecular weight of 500–3000 g / mol.

5. The self-healing, hydrophobic, quick-drying polyurethane membrane waterproof coating according to claim 1, characterized in that: The microencapsulated isocyanate latent curing agent uses polyurea or polyurethane as the shell material and aliphatic or alicyclic polyisocyanate as the core material, with a particle size of 5-30 μm.

6. The self-healing, hydrophobic, quick-drying polyurethane membrane waterproof coating according to claim 1, characterized in that: The nano-silica aerogel slurry is a pre-dispersion slurry of hydrophobic aerogel in a composite solvent, with a solid content of 10-25%, an original aerogel particle size of 20-50 nm, and a specific surface area of ​​600-1000 m². 2 / g.

7. The self-healing, hydrophobic, quick-drying polyurethane membrane waterproof coating according to claim 1, characterized in that: The inorganic flame retardant synergist includes at least one of aluminum hydroxide and reactive phosphorus-containing flame retardant polyol; the reactive phosphorus-containing flame retardant polyol has a hydroxyl value of 200-400 mg KOH / g and a phosphorus content of 8-15 wt%.

8. The self-healing, hydrophobic, quick-drying polyurethane membrane waterproof coating according to claim 1, characterized in that: The composite solvent is at least three of acetone, ethyl acetate, xylene, and N,N-dimethylformamide; wherein the proportion of low-boiling-point solvents with a boiling point ≤80℃ is ≥50%, and the proportion of medium- and high-boiling-point solvents with a boiling point ≥130℃ is 10-25%.

9. The preparation method of the self-healing hydrophobic quick-drying polyurethane membrane waterproof coating according to any one of claims 1-8, characterized in that, Includes the following steps: (1) Add nano silica aerogel slurry, additive nitrogen and phosphorus intumescent flame retardant, charring agent, inorganic flame retardant synergist, and coloring material to a portion of the composite solvent, disperse at 1000-1500 rpm for 30-40 minutes until the fineness is ≤25μm to obtain pre-dispersed slurry; (2) Add the main resin, remaining solvent, functional additives, and reactive flame-retardant polyol, and disperse at 800-1000 rpm for 15-20 minutes; (3) Cool down to 400-600 rpm and ≤40℃, then add silane-terminated polyetheramine, microcapsule latent curing agent and pre-dissolved F-POSS solution in sequence, and disperse for 5-10 minutes; (4) Filter the material through a 200-mesh filter to obtain the final product.

10. The application of the self-healing hydrophobic quick-drying polyurethane coating according to any one of claims 1-8 in the waterproofing and closed-cell treatment of polyurethane sponge wave-absorbing materials, characterized in that: The spraying application uses an HVLP spray gun, which is cured at room temperature. The HVLP spray gun has a nozzle diameter of 1.5-2.5mm, a spraying air pressure of 1.5-3.0 bar, a spraying distance of 15-30cm, 2-4 spray passes, a film thickness of 10-25μm per pass, and a flash-off time of 3-8 minutes between passes. The spraying environment temperature is 15-35℃, and the relative humidity is 40-80%.